2008
DOI: 10.5081/jgps.7.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of Various Interpolation Algorithms for Grid-Based Single Shell Ionospheric Model Over Indian Region

Abstract: Future Satellite Based Navigation Systems based on GPS, like US Wide Area Augmentation Sysytem (WAAS), are of global interest to the scientific community. Precise estimation of ionospheric delay is most crucial for successful implementation of the systems. Due to the complex ionospheric structure and large variation of Total Electron Content (TEC) in low latitudes, it is necessary to compare and validate the efficiency of the existing algorithms in this region. In this study, performances of the various interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…PROMINENT EXISTING IONOSPHERIC TIME-DELAY MODELS Because of the complex structure and dynamic nature of the ionosphere, the performances of the models are not uniform, especially at equatorial and low-latitude regions. The suitability and performance of ionospheric delay models can vary when implemented globally, regionally, and locally [13]. In view of this, for comparison and evaluation of the proposed anisotropic IDW with Jackknife technique, three prominent models, namely, Kriging, spline, and MPF, are considered.…”
Section: Anisotropic Idw With Jackknife Techniquementioning
confidence: 99%
“…PROMINENT EXISTING IONOSPHERIC TIME-DELAY MODELS Because of the complex structure and dynamic nature of the ionosphere, the performances of the models are not uniform, especially at equatorial and low-latitude regions. The suitability and performance of ionospheric delay models can vary when implemented globally, regionally, and locally [13]. In view of this, for comparison and evaluation of the proposed anisotropic IDW with Jackknife technique, three prominent models, namely, Kriging, spline, and MPF, are considered.…”
Section: Anisotropic Idw With Jackknife Techniquementioning
confidence: 99%
“…There are several ionospheric models currently being studied and developed. Out of these, the main models are the grid-based single-shell model [2][3][4], the two-shell model [5] and the Klobuchar model [6]. The Klobuchar model is a simplistic empirical model and is currently being utilised by the GPS users for correcting the ionospheric delay.…”
Section: Introductionmentioning
confidence: 99%
“…Flow chart of prediction methodology www.ietdl.org STEC is obtained. The detailed description of pre-processing of the TEC is provided by Shukla et al[4,5].…”
mentioning
confidence: 99%
“…Other techniques like Kriging are also proposed for the next generation of WAAS [10][11][12]. Shukla et al [9] in their study have found that both at the IGP and the user side, Ordinary Kriging is more suitable for the Indian region among the various algorithms tested. On the basis of the results from their study, two combinations have been considered to reconstruct the Slant Total Electron Content (STEC) for the present analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For single-frequency users of GPS, the ionosphere is the largest source of error in estimation of user position. Due to the presence of the Equatorial Ionospheric Anomaly (EIA) over the Indian region [7], the Planar Fit, which is currently used by WAAS [8], does not provide the required accuracy and integrity [9]. Other techniques like Kriging are also proposed for the next generation of WAAS [10][11][12].…”
Section: Introductionmentioning
confidence: 99%